Short-Term Risk for Stroke Is Doubled in Persons With Newly Treated Type 2 Diabetes Compared With Persons Without Diabetes: A Population-Based Cohort Study - Jeerakathil, Thomas; Johnson, Jeffrey A.; Simpson, Scot H.; Majumdar, Sumit R. (Stroke (1970), 2007)
Background and Purpose— Cardiovascular risk factors are suboptimally treated in diabetes, possibly because of the impression that there is a long delay between diagnosis and the development of macrovascular complications such as stroke. We determined the incidence of stroke in people newly treated for type 2 diabetes. Methods— We conducted an inception cohort study with the use of linked administrative databases from Saskatchewan Health. Subjects entered the type 2 diabetes cohort on receipt of their first prescription for an oral antidiabetic drug. We defined incident stroke as any hospital admission with International Classification of Diseases, Ninth Revision, codes 430 to 438 inclusive. Age-standardized incidence rates were compared between the diabetes cohort and the general population. Results— There were 12 272 subjects in the diabetes cohort, the mean±SD age was 64±13.6 years, and 55% were male. During a mean 5-year follow-up, 9.1% of the diabetes cohort had a stroke. The age-standardized incidence rate for stroke was 642 per 100 000 person-years in subjects with diabetes, compared with 313 per 100 000 person-years in the general population (rate ratio=2.1, 95% CI=1.8 to 2.3). The relative short-term risk for stroke in the diabetes cohort compared with the general population ranged from 1.8 (95%=CI 1.6 to 1.9) in persons >75 years to 5.6 (95% CI=2.5 to 9.3) in the 30- to 44-year category. Conclusions— The risk of stroke is high within 5 years of treatment for type 2 diabetes and more than double the rate for the general population. This further supports the need for aggressive early cardiovascular risk factor management in type 2 diabetes.